Leveraging Endowment Funds for Startup Growth: Models and Case Studies - Hassiba Almi; Raed Awashreh (Journal of Excellence for Economics and Management Research, 2025)
For years, endowment funds have been the basis of financial stability for universities and charitable organizations, providing key resources necessary to support academic, research, and philanthropic initiatives. A significant shift in recent years has been allocating these funds to stimulate startup growth and increase the overall economic impact. It covers many mechanisms through which an endowment fund can actively invest in startups, including direct investment, venture capital partnerships, and creative, impact-oriented methodologies. The current research will closely examine several successful cases of endowment strategies at Yale and Stanford within international contexts, discussing Russian universities' challenges and outlining immense opportunities and complex challenges related to early-stage venture investment. That is, investments in startups can yield considerable financial returns; at the same time, however, they contain many significant hazards like the illiquidity and volatility of markets. To avoid these risks, endowment managers must utilize several strategies, including but not limited to diversification, staged investing, and due diligence.